Optimizing The Diagnosis Of Patients With Metabolic-Associated Steatohepatitis - Mamajonov Islombek Sardorbek ugli; Yaminova Nafisa Khaydaraliyevna (Zien Journals, 2025)
Metabolic-associated steatohepatitis, abbreviated as MASH, represents an inflammatory and potentially progressive form of metabolic dysfunction-associated steatotic liver disease, abbreviated as MASLD. Because symptoms are often absent until advanced disease develops, the central diagnostic challenge is not merely detecting steatosis, but identifying the subgroup at risk for clinically meaningful outcomes, especially advanced fibrosis. In routine care, liver biopsy remains the reference standard for confirming steatohepatitis, grading activity, and staging fibrosis, yet it is invasive, costly, and impractical for population-level case finding. As a result, contemporary diagnostic optimization increasingly relies on structured, stepwise strategies that combine simple blood-based fibrosis scores, imaging-based elastography, and selective use of advanced modalities, supported by clear referral pathways across primary care, diabetology, obesity services, and hepatology
Keywords: metabolic-associated steatohepatitis; metabolic-associated steatohepatitisnoninvasive tests